"Amazing Rapidity": Time, Public Credit, and David Hume's Political Discourses. Issue 1 (1st June 2019) - CORREDERA, EDWARD JONES
Abstract : This article explores David Hume's views on public credit, the state, and geopolitics as outlined in his Political Discourses. By drawing attention to Hume's analysis of the speed of political economic dynamics, the article suggests the philosopher feared that public credit, a crucial source of eighteenth-century European economic growth, fundamentally revolutionized the pace of social relations, the mechanics of the state, and European geopolitics at large. Hume's study of public credit highlighted its role in reshaping eighteenth-century visions of time, and the philosopher's disappointment with his own solution, in turn, reinforces the need to consider the multifaceted effects of public credit in the modern world.